Teori Limit Muhammad Syahrur Dalam Studi Islam - Adji Pratama Putra (CV. ULIL ALBAB CORP, 2022)
This paper want to describe the methodology and application of Muhammad Syahrur’s theory in Islamic law. the method of this paper used library research. At the application level, Syahrur offers a limit theory which is described as God’s command expressed in the Qur’an and Sunnah to provide a minimum and maximum limit for all human action. Syahrur give an example of the application of limit theory which was developed into six, there are: the position of the minimum limit, the position of the maximum limit, the position of the minimum and maximum limits simultaneously, the position of the minimum and maximum limits simultaneously at one point, the position of the maximum limit with one point approaching a straight line without contact, and the position of the ‘positive’ maximum limit may not be crossed and the negative lower limit may be crossed.